Pengaruh Dosis Enzim Papain terhadap Rendemen dan Kualitas Virgin Coconut Oil (VCO) - Iskandar, Ahmat; Ersan, Ersan; Edison, Rachmad (Politeknik Negeri Lampung, 2015)
Virgin Coconut Oil (VCO) is the coconut oil that is produced naturally without chemicals and heating process. Papain enzyme is a protease that is used in the fermentation of milk serves as a catalyst in the manufacture of the VCO. The main of the research is to determine the dose of enzyme papain that can produce the highest yield of VCO and determine the effect of papain enzyme dosage on the quality of the VCO. This research used a randomized block design (RBD) by using the enzyme papain treatment 0%, 0:03%, 0:06%, 0:09%, 0:12%, and 0:15% and it was repeated for three times. The result of the study treatment dose is 0.15%. The enzyme papain produces the highest yield of 31.53%. Based on the BSN about the quality standard ISO VCO No.7381: 2008 include moisture content, free fatty acids, color, and aroma of the VCO papain enzyme. And the result of the treatment did not affect the quality of the VCO.Keywords : fermentation, papain enzyme, VCOPermalink: http://jurnal.polinela.ac.id/index.php/AIP/article/view/21